The Analysis Study of Diagnosis and Management of Epitaxis :A Comprehensive Systematic Review - Yusniar; Sayid Najibullah; Syarifah Srimulasiyah (International Medical Journal Corp. Ltd, 2024)
Background: Epistaxis, or nasal haemorrhage, is a common and potentially serious clinical presentation that can range from a minor inconvenience to a life-threatening emergency. This systematic review aims to provide a comprehensive analysis of the diagnosis and management of epistaxis, emphasizing the interplay between epidemiological factors, anatomical considerations, and clinical risk assessment. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Epistaxis is a multifactorial condition influenced by local and systemic factors, including comorbidities, medication use, and blood markers. Comprehensive treatment, such as effective initial management, bleeding point identification, and control of hypertension and anemia, is essential for improving outcomes. NOACs offer promising alternatives but require careful treatment consideration.